A prospective, open, comparative study of 5% potassium hydroxide solution versus cryotherapy in the treatment of genital warts in men - Caio Lamunier de Abreu Camargo; Walter Belda Junior; Luiz Jorge Fagundes; Ricardo Romiti (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: Genital warts are caused by human papillomavirus infection and represent one of the most common sexually transmitted diseases. Many infections are transient but the virus may recur, persist, or become latent. To date, there is no effective antiviral treatment to eliminate HPV infection and most therapies are aimed at the destruction of visible lesions. Potassium hydroxide is a strong alkali that has been shown to be safe and effective for the treatment of genital warts and molluscum contagiosum. Cryotherapy is considered one of the most established treatments for genital warts. No comparative trials have been reported to date on the use of potassium hydroxide for genital warts. OBJECTIVE: A prospective, open-label, randomized clinical trial was conducted to compare topical potassium hydroxide versus cryotherapy in the treatment of genital warts affecting immunocompetent, sexually active men. METHODS: Over a period of 10 months, 48 patients were enrolled. They were randomly divided into two groups and selected on an alternative basis for either potassium hydroxide therapy or cryotherapy. While response to therapy did not differ substantially between both treatment modalities, side effects such as local pain and post-treatment hypopigmentation were considerably more prevalent in the groups treated using cryotherapy. Result: In our study, potassium hydroxide therapy proved to be at least as effective as cryotherapy and offered the benefit of a better safety profile. CONCLUSION: Topical 5% potassium hydroxide presents an effective, safe, and low-cost treatment modality for genital warts in men and should be included in the spectrum of therapies for genital warts.